Recanalization of Chronic Total Occlusions in Patients With Previous Coronary Bypass Surgery and Consideration of Retrograde Access via Saphenous Vein Grafts. (July 2016) - Dautov, Rustem; Manh Nguyen, Can; Altisent, Omar; Gibrat, Claire; Rinfret, Stéphane
Abstract : Background—: The prevalence of native coronary chronic total occlusions (CTOs) after coronary artery bypass grafts (CABGs) is higher than in non-CABG population. We examined outcomes of CTO percutaneous coronary intervention (PCI) post-CABG versus without CABG. Then, we looked at feasibility and outcomes of retrograde CTO PCI via patent or occluded saphenous vein graft. Methods and Results—: We compared patient and procedural characteristics of 470 CTO cases treated from January 2010 to December 2015 depending on history of CABG. We assessed major adverse cardiac events, including cardiac death, myocardial infarction, ischemia-driven target-vessel revascularization, or reocclusion 1 year after successful CTO PCI in patients treated before February 2015. Post-CABG patients (175 cases) had a higher J-CTO score (2.5 versus 2.1; P =0.002). In-hospital complications were similar, although the incidence of contrast-induced nephropathy was higher in post-CABG patients (4.6% versus 1%; P =0.01). With multivariable analysis, post-CABG status was associated with higher incidence of 1-year major adverse cardiac event (hazards ratio=2.2; P =0.02). As a second level analysis, we looked at the feasibility and safety of CTO PCI via saphenous vein grafts (19% of post-CABG cases) versus collateral channels (36%) versus with an antegrade-only approach (45%), and assessed short-term outcomes and complications. High success was achieved in the saphenous vein graft group. In-hospital events were similar in the 3 groups. Conclusions—: Post-CABG CTO PCI is associated with similar high success and low complications compared with CTO PCI in patients who never had CABG. However, it is associated with higher recurrent events at 1 year. To achieve high success rate, use of saphenous vein grafts as retrograde conduits seems to be safe and effective.